2013
DOI: 10.1111/sum.12096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crop residue biochar on soil acidity amelioration in strongly acidic tea garden soils

Abstract: Strongly acidic soil (e.g. pH < 5.0) is detrimental to tea productivity and quality. Wheat, rice and peanut biochar produced at low temperature (max 300 °C) and differing in alkalinity content were incorporated into Xuan‐cheng (Ultisol; initial pHsoil/water = 1/2.5 4.12) and Ying‐tan soil (Ultisol; initial pH soil/water = 1/2.5 4.75) at 10 and 20 g/kg (w/w) to quantify their liming effect and evaluate their effectiveness for acidity amelioration of tea garden soils. After a 65‐day incubation at 25 °C, biochar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 32 publications
6
42
0
Order By: Relevance
“…However, biochar amendment had no significant influence on cumulative N 2 O emissions during the experimental period and even slightly increased cumulative N 2 O by 7.9-18.3 % in the CP group treatments (Tables 3a, 4). Thus, the mitigating effect of biochar amendment on N 2 O emissions did not work in the intensively managed vegetable field in this study, which is in consistent with previous short-term laboratory incubation results in acidic soils (Yuan and Xu, 2011;Wang et al, 2014). This finding may firstly be due to the decrease in soil pH in the treatments amended with biochar (Table 2).…”
Section: Effects Of Biochar On N 2 O Emissions and Vegetable Yieldsupporting
confidence: 90%
“…However, biochar amendment had no significant influence on cumulative N 2 O emissions during the experimental period and even slightly increased cumulative N 2 O by 7.9-18.3 % in the CP group treatments (Tables 3a, 4). Thus, the mitigating effect of biochar amendment on N 2 O emissions did not work in the intensively managed vegetable field in this study, which is in consistent with previous short-term laboratory incubation results in acidic soils (Yuan and Xu, 2011;Wang et al, 2014). This finding may firstly be due to the decrease in soil pH in the treatments amended with biochar (Table 2).…”
Section: Effects Of Biochar On N 2 O Emissions and Vegetable Yieldsupporting
confidence: 90%
“…The corrective effect of soil acidity, according to Verheijen et al (2010), is one of the most probable mechanisms to increase crop yields after application of biochar to the soil. According to Wang et al (2014), the main factors in neutralization of soil acidity are the association of H + ions with the biochar and decarboxylation processes. In this respect, a study of Petter et al (2012) showed that the positive effect of application of coal on the soil pH increased with increased biochar doses.…”
Section: Soil Chemical Characteristicsmentioning
confidence: 99%
“…Although biochar application has shown some variable results, depending on soil type, biochar feedstock, biochar pyrolysis temperature, and other environmental factors; there are a number of potential positive aspects associated with the use of biochar as a soil amendment, including increased soil nutrient availability and uptake by plants (Sigua, Novak, Watts, Johnson, & Spokas, ; Zornoza, Moreno‐Barriga, Acosta, Muñoz, & Faz, ); enhanced organic and inorganic fertilizers use efficiency (Schulz & Glaser, ); increased soil mineral N (NH 4 and NO 3 ) retention (Clough, Condron, Kammann, & Müller, ); reduced nutrient losses and fertilizer demand (Ding et al, ); improved soil physical properties (soil water holding capacity, soil aeration, bulk density, porosity, aggregate stability, infiltration rate, and hydraulic conductivity; Atkinson, Fitzgerald, & Hipps, ; Mukherjee & Lal, ); increased base saturation and liming effect on acidic soils (Wang et al, ); stabilization of heavy metals and reduced bioavailability to plants growing in contaminated soils (Ahmad et al, ; Paz‐Ferreiro, Plasencia, Gascó, & Méndez, ); stimulation of microbial populations and functioning (Zhu, Chen, Zhu, & Xing, ); increased crop performance and productivity (Jeffery, Verheijen, van der Velde, & Bastos, ); enhanced symbiotic N fixation in legumes (Mia et al, ); reduced salinity, drought, and heat stresses impact on plant growth and soil properties (Ali et al, ; Drake, Cavagnaro, Cunningham, Jackson, & Patti, ; Fahad et al, ). In conjunction with chemical fertilizers, biochar improves the nutrient use efficiency of plants by enhancing soil nutrient retention for a longer period of time, and via the slow release of nutrients according to plant requirements (DeLuca, MacKenzie, & Gundale, ).…”
Section: Introductionmentioning
confidence: 99%